2017
DOI: 10.1136/jim-2017-000480
|View full text |Cite
|
Sign up to set email alerts
|

End-Stage Renal Disease versus Death in a Portuguese Cohort of Elderly Patients: An Approach using Competing Event Analysis

Abstract: Chronic kidney disease (CKD) is higher in elderly, but mortality outweighs the risk of end-stage renal disease (ESRD). Our aim was to identify prognostic markers for ESRD or death in elderly CKD, within a competing-risk analysis. This is a longitudinal study of consecutive newly referred patients with CKD ages 65 years, followed until the time of the first event (ESRD or death), using a competing-risk analysis. A modified Charlson Comorbidity Index (mCCI) was subdivided into subgroups (0-2, 3-4, ≥5). Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…When we designed our longitudinal cohort study, the main objective was to identify the main predictors for CKD progression and death in elderly CKD patients referred to our outpatient department9. In this report we analyzed their baseline characteristics, cardiovascular risk profile, and cardiovascular disease prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When we designed our longitudinal cohort study, the main objective was to identify the main predictors for CKD progression and death in elderly CKD patients referred to our outpatient department9. In this report we analyzed their baseline characteristics, cardiovascular risk profile, and cardiovascular disease prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, we started to follow a cohort of elderly patients until the occurrence of the first event (ESKD or death)9. In this report we describe their baseline demographic and clinical characteristics, with particular emphasis for the cardiovascular disease burden, to define improved strategies of care.…”
Section: Introductionmentioning
confidence: 99%
“…These results are slightly superior to those found in previous studies. [26][27][28][29] We can speculate about the reasons for this difference, namely our patients were older and demanded urgent start hemodialysis which are two known conditions for worse outcomes. Nonetheless, age at dialysis start, did not modified the association between frailty, comorbidity, and death.…”
Section: Discussionmentioning
confidence: 93%
“…Only a few studies investigated mortality and kidney prognosis in elderly CKD patients, 9,18–21 and the incidence of KFRT and death varies. This may be due to differences in patient backgrounds, such as race, baseline kidney function and prevalence of proteinuria, as well as differences in treatment strategies and observation periods.…”
Section: Discussionmentioning
confidence: 99%
“…In a French prospective observational study of 155 CKD patients aged 80 years and older with CKD stages G3b to G5, the 3‐year probabilities of death and KFRT was 27% and 11%, respectively 19 . A Portuguese study investigating the prognosis of 416 patients with CKD aged 65 years or older found that 8.7% of patients progressed to KFRT and 24.8% died during a median follow‐up of 3.6 years 20 . In our study, the cumulative incidence of KFRT and death at 5 years was 47% and 12%, which is higher incidence of KFRT, and lower mortality compared to the previous reports.…”
Section: Discussionmentioning
confidence: 99%